DETERMINANTS OF SOLVENCY IN SHARIA LIFE INSURANCE: THE ROLE OF LIQUIDITY, INVESTMENT, CLAIMS EXPENSES, AND LEVERAGE - Salwa Tasya Aqilah; Siti Zulaikha; Alhabshi, Syed Othman (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
This study aims to analyse the effects of liquidity, investment returns, claim expenses, and leverage on the solvency of Sharia life insurance companies during the 2019–2023 period, both partially and simultaneously. Risk-Based Capital (RBC) is used as an indicator of the financial health of insurance companies, while liquidity, investment returns, claim expenses, and leverage serve as the independent variables tested. This study adopts a quantitative approach using panel data regression with the Random Effects Model (REM) to examine the relationships among variables. The results show that, partially, liquidity has a significant positive effect on solvency, while leverage has a significant negative effect. Meanwhile, investment returns show an insignificant negative effect, and claim expenses show an insignificant positive effect on the solvency of Sharia life insurance companies. Simultaneously, liquidity, investment returns, claim expenses, and leverage have a significant effect on solvency. The findings imply that both Sharia life insurers and regulators need to strengthen risk-based supervision, particularly in managing current assets and controlling debt usage, to ensure long-term financial stability.